Serum microRNAs explain discordance of non-alcoholic fatty liver disease in monozygotic and dizygotic twins: a prospective study. Issue 9 (22nd May 2015) - Zarrinpar, Amir; Gupta, Shakti; Maurya, Mano R; Subramaniam, Shankar; Loomba, Rohit
Abstract : Objective: In the setting where two individuals are genetically similar, epigenetic mechanisms could account for discordance in the presence or absence of non-alcoholic fatty liver disease (NAFLD). This study investigated if serum microRNAs (miRs) could explain discordance in NAFLD. Design: This is a cross-sectional analysis of a prospective cohort study of 40 (n=80) twin-pairs residing in Southern California. All participants underwent a standardised research visit, liver MRI using proton-density fat fraction to quantify fat content and miR profiling of their serum. Results: Among the 40 twin-pairs, there were 6 concordant for NAFLD, 28 were concordant for non-NAFLD and 6 were discordant for NAFLD. The prevalence of NAFLD was 22.5% (18/80). Within the six discordant twins, a panel of 10 miRs differentiated the twin with NAFLD from the one without. Two of these miRs, miR-331-3p and miR-30c, were also among the 21 miRs that were different between NAFLD and non-NAFLD groups (for miR-331-3p: 7.644±0.091 vs 8.057±0.071, respectively, p=0.004; for miR-30c: 10.013±0.126 vs 10.418±0.086, respectively, p=0.008). Both miRs were highly heritable (35.9% and 10.7%, respectively) and highly correlated with each other (R=0.90, p=2.2×10 −16 ) suggesting involvement in a common mechanistic pathway. An interactome analysis of these two miRs showed seven common target genes. Conclusions: Using a novel human twin-study design, we demonstrate that discordancy in liver fat content between the twins can be explained by miRs, and that they are heritable.